Supertall : how the world's tallest buildings are reshaping our cities and our lives. - Al, Stefan (New York : W.W. Northon & Company, 2022)
"The global boom in skyscrapers-why it's happening now, how they're made, and what they do to cities and people. We are living in a new urban age and its most tangible expression is the "supertall": megastructures that are dramatically bigger, higher, and more ambitious than any in history. In Supertall, TED Resident Stefan Al-himself an experienced architect who has worked on some of the largest buildings in the world-reveals the advancements in engineering, design, and data science that have led to this worldwide boom. Using examples from the past (the Empire State Building, St. Paul's Cathedral, the Eiffel Tower) and present (Dubai's Burj Khalifa, London's Shard, Shanghai Tower), he describes how the most remarkable skyscrapers have been designed and built. He explores the ingenious technological innovations-in cement, wind resistance, elevator design, and air-conditioning-that make the latest megastructures a reality. And he examines the risks of wealth inequality, carbon emissions, and contagion they yield while arguing for a more sustainable, resilient, and equitable built environment for everyone"--
boek
Keywords: Skyscrapers; Architecture and technology; Architecture and society; Architecture -- Environmental aspects